Methacrylate‐Modified Gold Nanoparticles Enable Noninvasive Monitoring of Photocrosslinked Hydrogel Scaffolds. Issue 7 (7th July 2022) - Li, Lan; Gil, Carmen J.; Finamore, Tyler A.; Evans, Connor J.; Tomov, Martin L.; Ning, Liqun; Theus, Andrea; Kabboul, Gabriella; Serpooshan, Vahid; Roeder, Ryan K.
Abstract : Biofabrication In article number 2200022, Ryan K. Roeder and co‐workers introduce photopolymerizable nanoparticles that can be incorporated into bioinks when bioprinting scaffolds. The nanoparticles are covalently linked to the hydrogel network enabling noninvasive, longitudinal monitoring of surgical placement, degradation, and nanoparticle release by computed tomography.